Pharmacokinetics and Bioequivalence of Two Formulations of Febuxostat 40-Mg and 80-Mg Tablets: A Randomized, Open-Label, 4-Way Crossover Study in Healthy Chinese Male Volunteers. - Zhu Luo; Feng Nan; Jia Miao; Zhihui Chen; Mei Li; Maozhi Liang (PLoS ONE, 2016)
Unlabelled The present study aimed to investigate the pharmacokinetic properties of febuxostat in healthy Chinese male volunteers and evaluate whether the two formulations of febuxostat 40-mg and 80-mg tablets are bioequivalent. A randomized, open-label, 4-way crossover study was conducted in healthy Chinese male volunteers under fasting conditions. 24 eligible subjects were randomized in a 1:1:1:1 ratio to receive a single dose of test or reference formulation of febuxostat 40-mg or 80-mg tablet. The washout period between each administration was 1 week. Plasma febuxostat was quantified by a validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method. Tolerability was evaluated by monitoring adverse events, physical examinations, 12-lead ECG and laboratory tests. After single-dosing of 1 tablet of 40-mg febuxostat, the pharmacokinetic parameters of test and reference formulations were: Tmax 1.22±0.87 and 1.85±1.03 h, Cmax 1689.16±461.31 and 1613.80±608.43 ng·mL-1, AUC0-t 5139.87±1349.28 and 5517.91±2024.26 ng·mL-1·h, AUC0-∞ 5263.06±1339.16 and 5640.48±2040.22 ng·mL-1·h, t1/2 4.82±2.61 and 4.85±1.78 h, respectively. After single-dosing of 1 tablet of 80-mg febuxostat, the pharmacokinetic parameters of test and reference formulations were: Tmax 1.71±1.21 and 2.23±1.55 h, Cmax 2744.47±1157.44 and 2998.17±1200.13 ng·mL-1, AUC0-t 9634.03±2768.25 and 10467.95±3501.65 ng·mL-1·h, AUC0-∞ 9834.32±2730.51 and 10626.63±3504.08 ng·mL-1·h, t1/2 6.25±2.44 and 5.46±1.65 h, respectively. For single-dosing of 1 tablet of 40-mg febuxostat, 90% CIs for the test/reference ratio of AUC0-t, AUC0-∞ and Cmax were 89.79 to 102.55, 90.14 to 102.56 and 93.99 to 129.63, respectively. For single-dosing of 1 tablet of 80-mg febuxostat, 90% CIs for the test/reference ratio of AUC0-t, AUC0-∞ and Cmax were 86.67 to 100.00, 87.50 to 100.51 and 79.48 to 105.99, respectively. This single dose study revealed similar pharmacokinetic properties in healthy Chinese male volunteers as those found in Caucasic population. The test and reference febuxostat tablets formulations met the regulatory criteria for bioequivalence at 40-mg and 80-mg strengths in fasting healthy Chinese male volunteers. Trial registration Chictr.org ChiCTR-TTRCC-14004288.